easy!!!!!

Algebra Level 1

Factorize the expression: 9 x 2 6 a x + ( a 2 b 2 ) 9x^2-6ax +(a^2-b^2)

( 3 x a b ) ( 3 x a b ) (3x-a-b)(3x-a-b ) ( 3 x a + b ) ( 3 x a b ) (3x-a+b)(3x-a-b ) ( 3 x + a + b ) ( 3 x + a + b ) (3x+a+b)(3x+a+b)

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Paola Ramírez
Jan 16, 2015

Let m = a + b m=a+b and n = a b n=a-b

Then 9 x 2 6 a x + m n 9x^2-6ax+mn

( 3 x m ) ( 3 x n ) = 9 x 2 3 x m 3 x n + m n (3x-m)(3x-n)=9x^2-3xm-3xn+mn = 9 x 2 3 x ( a + b ) 3 x ( a b ) + a 2 + b 2 =9x^2-3x(a+b) -3x(a-b)+a^{2}+b^{2} = 9 x 2 6 a x + a 2 b 2 = 9x^2-6ax+a^2-b^2

So 9 x 2 6 a x + ( a 2 b 2 ) = ( 3 x a b ) ( 3 x a + b ) 9x^2-6ax+(a^2-b^2)=\boxed{(3x-a-b)(3x-a+b)}

Chew-Seong Cheong
Jul 16, 2017

9 x 2 6 a x + ( a 2 b 2 ) = 9 x 2 6 a x + a 2 b 2 = ( 3 x a ) 2 b 2 Using the indentity: x 2 y 2 = ( x + y ) ( x y ) = ( 3 x a + b ) ( 3 x a b ) \begin{aligned} 9x^2-6ax+(a^2-b^2) & = 9x^2-6ax+a^2-b^2 \\ & = ({\color{#3D99F6}3x-a})^2 - {\color{#D61F06}b}^2 & \small \color{#3D99F6} \text{Using the indentity: } x^2-{\color{#D61F06}y}^2 = (x+{\color{#D61F06}y})(x-{\color{#D61F06}y}) \\ & = \boxed{({\color{#3D99F6}3x-a}+{\color{#D61F06}b})({\color{#3D99F6}3x-a}-{\color{#D61F06}b})} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...